Conflito de usos da água e ocupação do solo da Bacia Hidrográfica do rio Pitimbu no município de Macaíba, RN - Barbosa, Joelson Kayto Feitosa (2006)
Due to the increasing activities and its disordered occupation, the catchment of the Pitimbu river is reason of concern for the population, since the river empties in the lagoon of the Jiqui where 30% of the water of this lagoon are caught for the supplying the city of Natal, playing an important fuction in the supply of water superficial for the capital of the Rio Grande do Norte. The superior stretch of the hydrography catchment of the Pitimbu river - Macaíba/RN, object of this study, is denoted by the eminently agricultural occupation with the use of the irrigated agriculture in the many properties that compose this stretch. Because of this becomes necessary to analyze the availability of the water resources in the catchment of the Pitimbu river, in the superior stretch, collating with the use and occupation of the existing terrain. The stretch in study was divided in eight points which had been performed tests throughout the water and analyzed the parameters physicist-chemistries and heavy metals that are praised by resolution CONAMA nº 357 e, visits in field with photographic survey for characterization of this verifying the situation where if it finds the river. The stretch presented some divergence in the parameters of pH and iron, however the results denote a characteristic of the region. The great amount of slide barrages throughout the river and the wet street was observed, had also verified near the edges the launching of garbage and, the great amount of aquatic vegetation. With this it is concluded that the water of the river can be used for human supplying, therefore inside presents a quality of drinking waters of the standards demanded for resolution CONAMA nº 357, in this way, the stretch in study could be adopted as an Envoiremental Area Protection (APA), to preserve and to guarantee, at least in this stretch, that its condition remains unchanged and continues to supply of permanent form a water of excellent quality